Adsorption of phenol by activated carbon in rotating packed bed: Experiment and modeling. (September 2018) - Li, Weiwei; Yan, Junjuan; Yan, Zhifeng; Song, Yuncai; Jiao, Weizhou; Qi, Guisheng; Liu, Youzhi
Graphical abstract: Highlights: The q in RPB could be enhanced about 1.4 times of that in convention packed bed. Freundlich model described better performance than other five ones. The kr in RPB could be improved by 1.48 times at high gravity factor of 44.68. Abstract: This work assessed the feasibility of adsorbing phenol in aqueous solution by activated carbon in rotating packed bed (RPB). The effects of high gravity factor, liquid spray density and initial phenol concentration on the adsorption amounts of phenol in RPB were experimentally investigated, which was about 1.4 times of that in convention packed bed. Furthermore, the experimental adsorption isotherms curves were simulated by varies of models to assist the selection of important and characteristic parameters for the designing process of RPB, including Langmuir, Freundlich, Elovich, Temkin, Fowler–Guggenheim and Kiselev. Among the above six models, Freundlich model exhibited the best performance with the correlation coefficient (R 2 ) of 0.9970 and average percentage errors (APE) of 0.241. Besides, the intraparticle diffusion model with the correlation coefficient (R 2 ) above 0.990 could well simulate the adsorption performance for variety of operation conditions in RPB. The intraparticle diffusion coefficient (kr ) in RPB could be improved 1.48 times of that in convention packed bed at high gravity factor of 44.68.